ANTIMICROBIAL PROPHYLAXIS IN MANAGEMENT OF URINARY-TRACT STONES BY EXTRACORPOREAL SHOCK-WAVE LITHOTRIPSY - IS IT NECESSARY - (:unkn) unknown (CAHNERS PUBL CO, 1995)
Objectives. In a prospective randomized study, we evaluated the incidence of urinary tract infections following extracorporeal shock-wave lithotripsy (ESWL) and the necessity of prophylactic antibiotic administration in patients treated with this modality. Methods. A total of 360 consecutive patients with renal and ureteric stones who had sterile urine before ESWL treatment and did not have any increased risk of infection received either a single dose of 400 mg of ofloxacin or no prophylaxis. Patients were followed by simple urine analysis and urine cultures together, with clinical evaluations. Results. Only 3 patients (0.8%) had positive urine cultures at 1 week after ESWL. Two of these patients were in the antibiotic prophylaxis group. Conclusions. The incidence of urinary tract infections after ESWL is extremely low, provided that patients have sterile urine before ESWL, and prophylactic antibiotics are not required.
Keywords: PHARMACOKINETICS; ANTIBIOTICS